Shock-induced H loss from pyroxene and maskelynite in a Martian meteorite and the mantle source δD of enriched shergottites. (15th January 2022) - Dudley, J.-M.; Peslier, A.H.; Hervig, R.L.
Abstract: Assessing the water abundance and hydrogen isotopic signature (δD) of the Martian interior dictates our understanding of the formation of inner solar-system planets, the origin of their volatiles, Martian volcanic history, and the potential for life-bearing environments on the surface of the red planet. Although several Martian meteorites, representing the planet's crust, have been analyzed before for this assessment, little is known about the effect of shock on recorded hydrogen (H) in their mineral phases. Here, hydrogen contents and isotopes are measured by secondary ion mass spectrometry (SIMS) in an enriched olivine-phyric shergottite, Larkman Nunatak (LAR) 06319, containing impact-melted zones. Systematic 100 μm-long traverses in pyroxene and maskelynite grains reveal decreases of hundreds of µg/g H2 O and increases in δD of thousands of ‰ towards the contact with impact-melted zones, which is interpreted as H diffusive loss during shock-melting. Diffusion modeling reveals that temperatures high enough to permit H diffusion following shock were maintained near the impact-melted zone for a few minutes. By comparison, the interior of pyroxenes > 200 μm away from impact-melted zones have some of the highest H content with 170–480 µg/g H2 O and the lowest δD with ∼ 300‰. The latter values, obtained on the most Mg-rich, i.e. earliest crystallized pyroxenes, are used to estimate that the enriched shergottite mantle source contains 300–1000 µg/g H2 O and has a δD of ∼ 300‰. This δD is similar to that of depleted shergottite and nakhlite mantle sources, but higher than Earth's upper mantle, suggesting slightly different water source materials for the two planets. The enriched shergottite mantle source has ∼ 10 times more water than that inferred for the depleted shergottite source and for Earth's upper mantle. The high water content and wide range of δD in olivine (from 90 µg/g H2 O and 2700‰ to 1350 µg/g H2 O and −14‰) is interpreted as overprinting by a combination of Martian and terrestrial surface alteration. Finally, the high δD recorded in the impact-melt produced glass (3350–4700‰), its moderate water content (100–230 µg/g H2 O), and the presence of vesicles, are likely the result of incorporation of Martian surficial material (ice and atmospheric gases) and degassing during shock melting. This study shows that shock can induce H loss from minerals, accompanied by > 1000‰ δD increases. Additionally, although it confirms that the Martian mantle may be heterogeneous in its water content, it implies that the Martian mantle is homogeneous within uncertainties for δD.